The consumer acceptance on Islamic banking in Malaysia - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Jumahat, Julianah (IDOSI Publications, 2017)
Banking play important role in world economic. Malaysia banking product and services grow tremendous for the past few years. There is many product and services type offered by bank. Beside conventional banking, Islamic banking offered an alternative way to customers. According to Department of Statistic Malaysia, Muslim percentage in Malaysia were about 60.4% from 29.8 million populations in Malaysia. However, the demand on Islamic banking product and services is still far behind the conventional banking. This study will investigate the acceptance toward Islamic banking product and services in Malaysia. The research methodology will be base on secondary data from previous research and new data will be collected based on quantitative study.In the conclusions, This paper will give some recommendations on how to improved acceptance toward Islamic Banking in Malaysia.